1994
DOI: 10.1007/bf01743306
|View full text |Cite
|
Sign up to set email alerts
|

A general optimization strategy for sound power minimization

Abstract: A general approach for minimizing radiated acoustic power of a baffled plate excited by broad band harmonic excitation is given. The steps involve a finite element discretization for expressing acoustic power and vibration analysis, analytical design sensitivity analysis, and the use of gradient-based optimization algorithms. Acoustic power expressions arc derived from the Rayleigh integral for plates. A general methodology is developcd for computing design sensitivities using analytical expressions. Results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
31
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 13 publications
0
31
0
Order By: Relevance
“…In one of these papers [15], a plate of optimized stepped thickness distribution con"rmed that even a weaker structure can radiate less sound than a sti!er structure. In that example, the "rst eigenfrequency of an engine cover plate was decreased while the radiated noise level was reduced by about 12 dB.…”
Section: Introductionmentioning
confidence: 98%
“…In one of these papers [15], a plate of optimized stepped thickness distribution con"rmed that even a weaker structure can radiate less sound than a sti!er structure. In that example, the "rst eigenfrequency of an engine cover plate was decreased while the radiated noise level was reduced by about 12 dB.…”
Section: Introductionmentioning
confidence: 98%
“…Indeed, this 'one-way' coupling is exploited in the proposed strategy in this work. Lamancusa (1993) discusses several choices of design variables and objective functions that have been used, and concludes that the choice of acoustic power as an objective function produces the most consistently improved designs; examples of works where sound power is optimized are Belegundu et al (1994), Koopman and Fahnline (1997), Constans et al (1998), Milsted et al (1993) and Du and Olhoff (2007). In the works of Koopman and Fahnline (1997) and Du and Olhoff (2007), general (i.e., valid for arbitrary structures) expressions for the sensitivities of the sound power with respect to design variables are derived, and subsequently used in the optimization strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Lang and Dym (1) studied an optimal acoustic design for sandwich panels using a pattern search method and showed that the average transmission loss of a panel may be improved over a range of frequency and that the optimization is realized by shifting up the symmetric coincidence frequency of the panel beyond the frequency range of interest. Belegundu et al (2) presented a general gradient-based optimization algorithm for minimizing the sound power radiated from baffled plates excited by single-frequency and broadband harmonic excitation. Their study was an attempt to determine the optimum thickness distribution of a plate in order to minimize the radiated acoustic power under excitation over a band of frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Gradient methods have the advantage of typically converging on an optimal solution quite rapidly if the objective function is well behaved. Belegundu et al (2) and Hambric (9) have reported that non-gradient optimization methods are attractive compared to gradient methods for structural optimization with respect to acoustic response because of the presence of multiple local minima.…”
Section: Introductionmentioning
confidence: 99%